2007
DOI: 10.1111/j.1439-0531.2007.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lamb Sucking on the Bacterial Flora of Teat Duct and Mammary Gland of Ewes

Abstract: We aimed (i) to determine differences in bacterial flora of teat duct and mammary gland of ewes before and after suckling, (ii) to evaluate factors potentially affecting those. We collected samples of teat duct material and mammary secretion from 11 ewes immediately before and after sucking by lambs, as well as 120 min later. We processed samples bacteriologically and compared changes in infection by the Sign Test. We isolated bacteria from 3.5% duct and 1.5% secretion samples before suckling. Respective figur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Other potential sources of bacteria include the nasopharynx of sucking lambs (Gougoulis et al ., 2008), staphylococci already present in the teat duct (Fragkou et al ., 2007) and staphylococci present on the udder skin (Mavrogianni et al ., 2007). Albenzio et al .…”
Section: Staphylococcal Mastitis In Sheepmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential sources of bacteria include the nasopharynx of sucking lambs (Gougoulis et al ., 2008), staphylococci already present in the teat duct (Fragkou et al ., 2007) and staphylococci present on the udder skin (Mavrogianni et al ., 2007). Albenzio et al .…”
Section: Staphylococcal Mastitis In Sheepmentioning
confidence: 99%
“…As Laukova and Marounek (1992) have isolated staphylococci form the upper alimentary tract of lambs, it is evident that the bacteria can transmit to the teat during sucking As the lower part of the teat comes into contact with the pharynx of the lamb (Titchen, 1977) the bacteria subsequently enter the duct; perhaps; the tongue of the lamb may ‘push’ the bacteria upwards into the duct. Isolation of the microorganism after only a short (1 min) sucking activity indicates the speed by which the whole process can take place (Gougoulis et al ., 2008). Staphylococci have been found as resident flora of the teat duct of healthy ewes (Fragkou et al ., 2007, Mavrogianni et al ., 2007).…”
Section: Staphylococcal Mastitis In Sheepmentioning
confidence: 99%
“…We postulate that as the lower part of the teat comes into contact with the pharynx of the lamb [ 28 ], the organism was attached thereon, subsequently entering into the duct; perhaps the tongue of the lamb might have “pushed” the bacteria upwards into the duct. In previous studies [ 29 ], we have presented evidence that bacteria can be transferred from the mouth of lambs to the teat duct of their dams even after a short (1 min) sucking activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have reported outbreaks where the incidence of clinical mastitis ranged from 30% to 50% (Lafi et al, 1998;Calavas et al, 1998), with an increased incidence of clinical mastitis being observed in the early lactation until weaning (Mork et al, 2007;Arsenault et al, 2008;Gougoulis et al, 2008). In the case of subclinical mastitis, a prevalence ranging from 5% to 30% has been found Contreras et al, 2003;Berthelot et al, 2006).…”
Section: Epidemiologymentioning
confidence: 99%